Peran Motivasi dan Disiplin Kerja Dalam Menciptakan Kinerja Karyawan (Studi Deskriptif pada Karyawan Pengujian Kendaraan Bermotor (PKB) Tandes Surabaya) - Purnomo, Benny; Untarini, Nindria (Seminar Nasional Manajemen, 2025)
This study aims to analyze the role of motivation and work discipline in creating employee performance. The research method used is the quantitative descriptive method. The population in this study were motor vehicle testing employees in Tandes Surabaya. The research sample was 42 ASN employees and Contract Employees (OS) of PKB Tandes Surabaya. The results of the study showed that the performance of motor vehicle testing employees in Tandes Surabaya was good, as indicated by an increase in the number of vehicles that passed the KIR test, reduced complaints from users, and the achievement of the target of increasing efficiency in the testing process. Likewise, the average employee has good work motivation and discipline. This is indicated by increased performance, compliance with work regulations and procedures, and active participation in activities that support the success of the work unit. Employees consider that high work motivation and discipline play a role in improving their performance. For this reason, the PKB Tandes Surabaya office needs to maintain employee work motivation through various means, such as providing competitive salaries and benefits, a comfortable work environment, performance awards, opportunities for development, and good communication, as well as providing trust and responsibility.